1975
DOI: 10.1029/ja080i016p02057
|View full text |Cite
|
Sign up to set email alerts
|

Identifications of the polar cap boundary and the auroral belt in the high-altitude magnetosphere: A model for field-aligned currents

Abstract: Using the OGO-5 GSFC-fluxgate magnetometer data, the polar cap boundary is identified in the high-altitude magnetosphere by a sudden transition from a dipolar field to' a more tail-like configuration. It is inferred that there exists a field-aligned current layer at the polar cap boundary. In the nightside magnetosphere the polar cap boundary is identified as the high-latitude boundary of the plasma sheet. The fieldaligned current flows downward to the ionosphere on the morning side of the magnetosphere and up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
46
0

Year Published

1976
1976
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(54 citation statements)
references
References 48 publications
8
46
0
Order By: Relevance
“…These results are summarized in a study by SUGIURA (1976a). SUGIURA (1975) andYA5UHARA et al (1975) both utilized polar orbiter magnetometer data to show that there was an excess of current into the ionosphere in the pre-noon quadrant and an excess of current out of the ionosphere in the dusk sector. Since that time there have been well documented definitive studies carried out by PoTEMRA (1976), andPOTEMRA (1976a, b) using magnetometer data from the Triad satellite which have been very useful in defining the patterns of fieldaligned current flow in more detail.…”
Section: Field-aligned Currents and Ionospheric Electrojet Currents Imentioning
confidence: 99%
“…These results are summarized in a study by SUGIURA (1976a). SUGIURA (1975) andYA5UHARA et al (1975) both utilized polar orbiter magnetometer data to show that there was an excess of current into the ionosphere in the pre-noon quadrant and an excess of current out of the ionosphere in the dusk sector. Since that time there have been well documented definitive studies carried out by PoTEMRA (1976), andPOTEMRA (1976a, b) using magnetometer data from the Triad satellite which have been very useful in defining the patterns of fieldaligned current flow in more detail.…”
Section: Field-aligned Currents and Ionospheric Electrojet Currents Imentioning
confidence: 99%
“…current layer presented in Figure 3 above is the same as that in the current layer ?ctected by Ogo 5 in the high altitude magnetosphere; see Figure 8 in Sugiura (1975) for a schematic current flow pattern. Thus we now believe that the current layer, observed by Triad at 800 km altitude is the same current layer as that detected by Ogo 5• As was discussed by Sugiura l (1975) the presence of this field-aligned current layer is more or less a permanent feature of the magnetosphere.…”
Section: Current Layer As a Permanent Featurementioning
confidence: 99%
“…Based on the Ogo 5 magnetometer results Sugiura (1975) has shown that the transition from the dipolar magnetospheric field to a more taillike field configuration often takes place rather suddenly and that this transition is accomplished by the existence of a field-aligned current layer at the polar cap boundary. He further showed that the directions -11 -of the field-aligned currents, i.e, toward the ionosphere on the morning side and away from it on the afternoon aide, match those of the fieldaligned currents observed at the higi-latitude boundary of the plasma sheet in the tail.…”
Section: Current Layer As a Permanent Featurementioning
confidence: 99%
See 1 more Smart Citation
“…Average spatial distributions of the transverse magnetic perturbations associated with FACs were presented by Armstrong and Zmuda (1975) and Zmuda and Armstrong (1974a,b) who used vector magnetic field data from the TRIAD spacecraft and by Sugiura (1975) using OGO 5 magnetometer data. The first spatial distribution of FACs was obtained from TRIAD magnetometer data and used an average over 439 orbits (Iijima and Potemra, 1976a,b).…”
Section: Introductionmentioning
confidence: 99%